Studies on the genus Chrysodema (Coleoptera: Buprestidae: Chrysochroinae) part II. - Frank, David (Zootaxa, 2022)
The second part of the study on the genus Chrysodema Laporte de Castelnau & Gory, 1835 is presented. All taxa are revised based on a comparative study of extensive material including types of all described taxa. Chrysodema (Chrysodema) eximia ‘complex’ is revised and the new C. antennata species-group is established in the subgenus Chrysodema s. str. Two new species and one new subspecies are described: Chrysodema (Chrysodema) holynskii sp. nov. from Philippines: Masbate Island; Chrysodema (Chrysodema) sekerkai sp. nov. from Indonesia: Bangkai, Peleng and Sulawesi islands; and Chrysodema (Chrysodema) antennata barriesi subsp. nov. from Philippines: Palawan Island. Lectotypes are designated for the following taxa to ensure their correct application and recognition in future: C. (C.) antennata Saunders, 1874; C. (C.) hebes Kerremans, 1892; C. (C.) intercostata Saunders, 1874 and C. (C.) obsoleta J. Thomson, 1879. All herein included taxa are illustrated with colour photographs of habitus and the male aedeagus. Keys and maps of distribution to all taxa in each revised species-group are presented.